Detailed modelling and simulation of single-phase transformers for research and educational purposes - Saif Sabah Sami; Mazin T. Muhssin; Zeyad Assi Obaid; Ali N. Hussain (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
COVID-19 pandemic, despite its devastating impact, accelerated the shift to e-learning in higher education. Particularly in the electrical machines courses, that often include laboratory experiments. However, no detailed models of transformers, developed in Simulink/MATLAB®, were reported in the literature. Hence, in this paper, a virtual laboratory consists of models of single-phase transformers was built for the first time. The proposed models are easy to use and modify, and allow all machines’ parameters to be altered for students to replicate easily to support and enhance the learning process of electrical machines courses. Consequently, the developed models are effective tools for educational and research purposes. Dynamic models of single-phase, two-winding, transformers and step-up and step-down auto-transformers were developed using Simulink/MATLAB®. Two different approaches for modelling were proposed, the block diagram representation and Simscape based models. The two modelling methods were validated against the built-in transformer model. The developed models have been successfully integrated into electrical engineering courses at Middle Technical University, Baghdad, Iraq. Therefore, all developed models are freely available online at a dedicated repository.